French legislation on occupational risks:: a framework adaptable to psychosocial risks - BADEL, Maryse (Journal of Human Sciences, 2023)
Psychosocial risks (RPS) are often addressed from the perspective of labor law, but more rarely from that of social security law. However, they pose major problems of legal qualification when it comes to compensating the employees who are victims, the realization of the risk most often resulting in a temporary or permanent work stoppage. What then are the legal qualifications possibly opened up by the Social Security legislation on occupational risks to accommodate these evils resulting from work? What compensation is provided to victims of PSR/professional risks and, above all, to what extent can intentional and inexcusable faults be mobilized to improve the compensation for the damage suffered by these employees who are sick at work? The communication proposes to answer these two series of questions, major from the point of view of legal concepts and practical issues.